Potensi Kombinasi Maggot, Kunyit dan Indigofera Sebagai Antioksidan Alternatif Imbuhan Pakan - Sri Purwanti; Nurhasmiati Nurhasmiati; Nancy Lahay; Jasmal A. Syamsu (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Abstract The purpose of this study is to find out how much antioxidant content combination maggot (Hermetia illucens), turmeric (Curcuma domestica) and Indigofera zollingeriana to be used as an alternative feed additive for poultry. This study used a complete randomized design with 6 treatments 3 replays using DPPH method with treatment P0 vitamin C (positive control), P1 (2,5% turmeric + 5% Indigofera + 25% larva BSF), P2 (2,5% turmeric+ 10% Indigofera + 20% larva BSF), P3 (2,5% turmeric + 15% Indigofera + 15% larva BSF), P4 (2,5% turmeric + 20% Indigofera + 10% larva BSF), P5 (2.5% turmeric + 25% Indigofera + 5% larva BSF). The observed parameters are antioxidant activity using orthogonal contrast tests and orthogonal polynomial tests. The results showed that the treatment had a very real effect (P<0.01) on antioxidant activity. Orthogonal contrast test results showed that the treatment of P0 (control) with the treatment of P1, P2, P3, P4 and P5 had a very noticeable effect (P<0.01) on antioxidant activity. Further tests of orthogonal polynomials showed that the highest antioxidant was in the P5 treatment (2,5% turmeric + 25% Indigofera + 5% larva BSF) 115.67%. It was concluded that a combination ofÂ 25% larva BSF (Hermetia illucens), 2,5% turmeric (Curcuma domestica) and 5% Indigofera zollingeriana can be used as an alternative feed additive source of antioxidants for poultry livestock. Keywords: Antioxidants, larva BSF, turmeric, Indigofera zollingeriana.